SOIL BIOGENICITY IN THE RHIZOSPHERE OF DIFFERENT WHEAT GENOTYPES UNDER THE IMPACT OF FERTILIZATION TREATMENT - Roljević Nikolić, Svetlana M; Dolijanović, Željko; Kovačević, Dušan; Oljača, Snežana; Majstorović, Helena (Journal of Agricultural Sciences (Belgrade), 2022)
The paper examines soil biogenicity from the aspect of the abundance of various physiological groups of microorganisms in the rhizosphere of four subspecies wheat, in three fertilization treatments in the organic farming system. A field experiment was conducted using a randomized complete block design with four replicates. It was carried out on the leached chernozem soil type in the period from 2009 to 2012. There was a significant variability in the abundance of the studied physiological groups of microorganisms between the subspecies wheat, as well as between the fertilization treatments. The rhizosphere of common wheat had the greatest abundance of mycorrhizal fungi (24.37 x 103 g-1). The soil samples from the rhizosphere of compactum wheat had the largest abundance of oligonitrophilic bacteria (361.47 x 105g-1) and amonificators (119.27 x 105g-1). There were no significant differences in the abundance of actinomycetes between the cultivars of common, compactum and durum wheat, but their lowest number was found in the spelt wheat cultivar (11.25 x 103g-1). The combined application of biofertilizer and organic fertilizer resulted in a significantly greater abundance of fungi (28.2%), amonificators (56.6%) and oligonitrophiles (14.6%) than in the control treatment, while a significant impact of biofertilizers was noticed only regarding amonificators (39.2%). The obtained results show that the selection of a suitable crop variety, accompanied by the application of appropriate fertilizer formulations, can affect the specific characteristics of the microbial community that represents a significant factor of soil fertility. This is particularly the case in organic farming, which relies completely on natural resources and processes.
Keywords: wheat; organic farming; biohumus; biofertilizer; fungi; actinomycetes; amonificators; oligonitrophiles